Screening and surveillance in hereditary gastrointestinal cancers: Recommendations from the European Society of Digestive Oncology (ESDO) expert discussion at the 20th European Society for Medical Oncology (ESMO)/World Congress on Gastrointestinal Cancer, Barcelona, June 2018. (November 2018) - Vangala, Deepak B.; Cauchin, Estelle; Balmaña, Judith; Wyrwicz, Lucian; van Cutsem, Eric; Güller, Ulrich; Castells, Antoni; Carneiro, Fatima; Hammel, Pascal; Ducreux, Michel; van Laethem, Jean-Luc; Matysiak-Budnik, Tamara; et al.
Abstract: Patients with hereditary gastrointestinal (GI) cancers represent a substantial fraction of the overall affected population. Although awareness for hereditary GI cancer syndromes is on the rise, identification of patients and measures of surveillance are often unclear in everyday clinical routine. Therefore, the European Society of Digestive Oncology expert discussion 2018 at the World Congress on Gastrointestinal Cancer focussed on screening and surveillance of hereditary colorectal, gastric and pancreatic cancers. An international panel of experts and opinion leaders developed the here presented recommendations based on published evidence and on profound clinical expertise to facilitate clinical routine in identification and caretaking of patients with familial GI cancers. Highlights: Hereditary causes account for a substantial fraction of gastrointestinal cancers. Family history remains the key for identifying patients and individuals at risk. Caretaking for patients and individuals at risk is a multidisciplinary approach. Genetic counselling should be offered before germline mutational analysis. Appropriate surveillance measures can prevent potentially fatal cancers.